Characterization of the lysogenic repressor (c) from transposable Mu-like bacteriophage D108. - Kukolj, G (Nucleic Acids Res, 1991)
The c gene products from related, transposable phages Mu and D108 encode lysogenic repressors which negatively regulate transcription and transposition. Using the gel shift assay to monitor c-operator specific DNA-binding activity, the 19.5 kDa D108 c repressor was purified to homogeneity. Sequence analysis of the N-terminus confirmed the identity of the purified protein as the repressor and ascribed its ATG initiation codon to base pair 864 from the D108 left end. Analytical gel filtration and dimethyl suberimidate cross-linking of repressor at 0.1-0.5 microM concentrations revealed that the repressor protein could form oligomers in the absence of its DNA substrate. From DNase I footprinting and gel mobility shift analyses, the D108 repressor only bound to two operators (O1 and O2) which, as in Mu, flank an Integration Host Factor (IHF) binding site. In contrast to Mu, an O3 site in D108 was not found. Moreover, D108 repressor first bound operator O2, while occupancy of O1 required higher protein concentrations. The implications of these results on the D108 regulatory system are discussed. IMAGES: